Immunization competence retention in medical students: a comparation between conventional lectures and lectures with simulations method - Hartono Gunadi; Rini Sekartini; Retno Asti Werdhani; Ardi Findyartini; Muhammad Arvianda Kevin Kurnia (Paediatrica Indonesiana, 2015)
Background Immunization is recognized as one of the strategies to reduce vaccine preventable diseases. Competency related to immunization are consequently important for medical students and the medical school needs to assure the competence acquisition. Objective To assess competence related to immunization and its retention following lectures with simulations compared to lectures only. Methods A quasi-experimental study was conducted to the 5th year students of University of Indonesia Medical School during the Child Adolescent Health Module in 2012-2013. The intervention group had lectures with simulations and the control group had lectures only. Immunization knowledge was assessed with a 30 multiple choice question (MCA) items performed before and after the module. Competence retention was assessed by MCQ (knowledge) and OSCE (skills) 2-6 months afterwards. Results Sixty eight subjects for each group with similar characteristics were analyzed. There was significant difference after module MCQ score between two groups. Competence retention in 2-6 months after module completion was better in intervention group, both for the knowledge (median MCQ score of 70.00 (range 37-93) vs. mean score of 58.01 (SD 12.22), respectively; P<0.001) and skill (OSCE mean scores of 75.21 (SD 10.74) vs. 62.62 (SD 11.89), respectively; P < 0.001). Proportion of subjects in the intervention group who passed both the MCQ and OSCE were also significantly greater. Conclusion Lectures with simulations are proved to be more effective in improving medical students’ immunization competence as well as its retention compared to lectures only approach.